The rectal insufflation is not the best administration route of ozone (Ozone Therapy Global Journal, 2013)
We read the letter entitled “Rectal insufflations are a valid way in ozonetherapy” by Martínez-Sánchez et al. (Revista Española de Ozonoterapia. 2012, Vol. 2, nº 1, pp. 233-235) as afeedback on our article “Oxygen-Ozone Therapy is at a Cross-Road” (Rev. Esp. Ozono. 2011,1(1): 74-86). As we have been involved in this topic for longer than two decades, we felt theduty to express some reservation about the validity of the ozone administration via rectal routeas well as the expanding use of infusing ozonated saline. It is obvious that the ozoneadministration via rectal route is the most simple and cheap way to administer ozone. However,while the physician intends to administer a total amount of 6 mg, he cannot be ever sure whichis the effective ozone dose because: i) in the colorectal lumen there are feces,mucopolysaccharides that variably react and neutralize some of the administered ozone; ii)part of the gas may be involuntarily eliminated. Moreover, it must be clear that the remainingozone is never absorbed by the rectal mucosa because it immediately reacts with the liningfluid. On the other hand, the generated H2O2 last only about 20 sec and only some peroxidationproducts can be absorbed and they have been measured in the portal and jugular veins. Tothe best of our knowledge, the experimental work conducted in rabbits in 2000 is the only onepublished clarifying this point.1 Therefore, the dose of ozone acting as a really effective prodrug remains uncertain and variable, and the procedure remains empirical. Moreover, in Europe atleast 40% of patients refuses the rectal administration.